2018
DOI: 10.1111/cod.12966
|View full text |Cite
|
Sign up to set email alerts
|

European Surveillance System on Contact Allergies (ESSCA): polysensitization, 2009–2014

Abstract: The varying prevalences of polysensitization across Europe most likely reflect differences in patient characteristics and referral patterns between departments. Known risk factors for polysensitization are confirmed in a European dermatitis population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 53 publications
2
21
2
1
Order By: Relevance
“…In particular, the percentage of males with contact dermatitis, was found to be between 11.8% and 40.8% with a median of 28.75%, while our results showed a male population of 31.29%. 15 Further on, OD manifested a minimum of 5.3% and a maximum of 47.6% in the European cohort study, while in our study we have found that 31.55% were diagnosed with OD. 15 At the same time, AD, HD, LD and FD manifested a minimum of 10.6%, 8.7%, 1.8% and 0.9% respectively, a maximum of 38.5%, 64.2%, 22.4% and 32.9% respectively and finally a median of 24.9%, 25.75%, 4.55% and 11.75% respectively.…”
Section: Discussioncontrasting
confidence: 45%
“…In particular, the percentage of males with contact dermatitis, was found to be between 11.8% and 40.8% with a median of 28.75%, while our results showed a male population of 31.29%. 15 Further on, OD manifested a minimum of 5.3% and a maximum of 47.6% in the European cohort study, while in our study we have found that 31.55% were diagnosed with OD. 15 At the same time, AD, HD, LD and FD manifested a minimum of 10.6%, 8.7%, 1.8% and 0.9% respectively, a maximum of 38.5%, 64.2%, 22.4% and 32.9% respectively and finally a median of 24.9%, 25.75%, 4.55% and 11.75% respectively.…”
Section: Discussioncontrasting
confidence: 45%
“…Figure shows a study flow chart. Overall, 86 416 patients had been tested with the baseline series in 2009 to 2014; 44 300 of these were documented by the use of winalldat software, and were thus utilizable for the present analysis. We considered only the most recent consultation if one patient had multiple consultations.…”
Section: Resultsmentioning
confidence: 99%
“…Another factor associated with MCAs was occupationally related dermatitis (OR 1.94), which had a similar strength as the factor active working adult age group (25‐59 years; OR 1.81). An explanation is the higher probability of allergen exposure through work (which may be undertaken in occlusive conditions and with pre‐existing skin irritation); this promotes sensitization …”
Section: Discussionmentioning
confidence: 99%
“…According to our observation, MCA patients usually present with widespread, long‐lasting and hard‐to‐treat eczema. The incidence of MCA patients varies among populations . Previous studies showed a higher prevalence of MCAs than expected in both general and dermatitis populations .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation